PECULIARITIES OF ORGANIZATION OF EFFECTIVE SYSTEM OF MANAGEMENT resource conservation AND ENERGY EFFICIENCY IN different INDUSTRIES OF THE ECONOMY - O. Astafyeva (Вестник университета)
The article considers possibilities of increase of resource and energy efficiency in different industries of the economy. Analyzed the stages of resource-saving management at the industry and regional levels. Identified key indicators to ensure resource efficiency and energy efficiency of subjects of economic activity. Directions of the efficient system of resource management and energy efficiency in industry of the Russian economy.